Probiotics [LGG-BB12 or RC14-GR1] versus placebo as prophylaxis for urinary tract infection in persons with spinal cord injury [ProSCIUTTU]: a randomised controlled trial - Toh, Swee-Ling (2021)
Study design: Randomised double-blind factorial-design placebo-controlled trial.